Use of bending tests and visual inspection for multi-scale experimental evaluation of chestnut timber beams stiffness - Sousa, Hélder S. (2016)
The assessment of existing timber structures requires the determination of the mechanical properties of the individual timber members, which is often obtained by visual grading combined with information of small clear wood specimens. The purpose of this work is to present the results obtained in a multi-scale experimental evaluation of 20 old chestnut (Castanea sativa Mill.) beams, aimed at defining the correlations between bending modulus of elasticity (MOE) in different scales of timber members in combination with visual grading. The results of bending tests, according to EN 408:2010, were statistically analyzed to obtain correlations of bending MOE between and within different scales size. The results of visual inspection according to UNI 11119:2004 regarding the presence and distribution of defects were considered for variation analysis of MOE, evidencing a significant variance between samples of different visual strength grades. Strong correlations within the same phase (coefficient of determination r2 from 0.82 to 0.89) and moderate to high correlations for different phases (r2 from 0.68 to 0.71) were found for bending MOE. Cumulative distribution functions for global MOE remained similar throughout the experimental phases. Moreover, percentage of segments attributed to a specific visual grade is given for each member and compared between scales.